Implementation of the Witness and Victim Protection Act for Victims of Personal Data Theft Crimes - Permana, Gabriel Riziq; Harmono , Harmono (Pelopor Publikasi Akademika, 2025)
The rapid development of information technology in Indonesia has also increased the risk of personal data theft through digital media. This research aims to analyze the effectiveness of legal protection for victims of personal data theft based on the prevailing legal framework in Indonesia, and to compare it with data protection regimes in other countries. The method employed is a normative juridical approach, utilizing both conceptual and comparative analyses. The findings indicate that legal protection for victims in Indonesia continues to face significant challenges, particularly due to weak law enforcement, limited supervisory authorities, and suboptimal remedies for victims. Data breach incidents occurring throughout 2025, including those involving digital financial and health service platforms, demonstrate that victims’ rights have not yet been adequately safeguarded. In contrast, regulatory frameworks such as the General Data Protection Regulation (GDPR) in the European Union and the Personal Data Protection Act (PDPA) in Singapore provide a more proactive and user-centric system of protection. Accordingly, it is essential to strengthen national policy by enacting and effectively implementing the Personal Data Protection Law, enhancing the capacity of law enforcement agencies, and fostering cross-sectoral synergy to establish a secure and equitable digital ecosystem.